2014
DOI: 10.4274/turkderm.78300
|View full text |Cite
|
Sign up to set email alerts
|

Otoimmün büllü hastalıkların klinik ve demografik özellikleri: 85 hastanın retrospektif analizi

Abstract: ÖzetAmaç: Otoimmün büllü hastalıklar, derideki spesifik antijenlere yönelik dokuda ya da kanda otoantikorların varlığı ile karakterize deri ve/veya mukoza tutulumu ile seyreden hastalıklar grubudur. Çalışmamızın amacı kliniğimize başvuran otoimmün büllü hastalıkların demografik ve klinik özelliklerini değerlendirmektir. Yöntem ve Gereçler: 2003-2011 yılları arasında kliniğimize başvuran klinik, histopatolojik ve immunopatolojik kriterlere dayanılarak otoimmün büllü hastalıklar tanısı konan hastalar retrospekti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
4
3
0
Order By: Relevance
“…Furthermore, the PV/BP ratio in our study was 0.96, and this ratio was reported to be between 1.1-1.5 in previous reports from Turkey. Although the demographic and clinical characteristics of ABD patients were in accordance with previous studies, most of the DH patients in our study were female (3,6,7,10,13). It is known that DH affects males more frequently, but the predominance of female patients was also reported if there was an accompanying autoimmune disease, as in our study (10,13).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the PV/BP ratio in our study was 0.96, and this ratio was reported to be between 1.1-1.5 in previous reports from Turkey. Although the demographic and clinical characteristics of ABD patients were in accordance with previous studies, most of the DH patients in our study were female (3,6,7,10,13). It is known that DH affects males more frequently, but the predominance of female patients was also reported if there was an accompanying autoimmune disease, as in our study (10,13).…”
Section: Discussionsupporting
confidence: 86%
“…In the literature, BP was reported as the most frequent ABD in developed countries, but in our country, it was the second most common ABD after PV. A significant increase in the number of patients has also been noted in recent years, probably due to prolongation of the lifespan (3,6,7). Furthermore, the PV/BP ratio in our study was 0.96, and this ratio was reported to be between 1.1-1.5 in previous reports from Turkey.…”
Section: Discussionsupporting
confidence: 70%
“…[5][6][7] In studies conducted in Turkey, in support of the literature, PV has been reported as the most frequently seen ABD, followed by BP. [1,[7][8][9] Similarly, in our study, the frequency was 51.4% for PV and 41.5% for BP.…”
Section: Discussionsupporting
confidence: 65%
“…
A utoimmune bullous diseases (ABDs) are a group of diseases characterized by vesiculobullous lesions in the mucosa and/or skin as a result of the development of autoantibodies against some target antigens present in the skin. [1,2] ABDs are divided into two main classes as intraepidermal and subepidermal ABDs depending on the level of bullae formation. The main event in intraepidermal ABDs is acantholysis, which is the separation of keratinocytes from autoantibodies developed against desmogleins, which are the intercellular adhesion molecules.
…”
mentioning
confidence: 99%
See 1 more Smart Citation